Portrait of Émile Duclaux (1900)
Portrait photograph of French microbiologist and chemist Émile Duclaux (1840-1904). Duclaux began assisting Louis Pasteur (1822-1895) in 1862. He became the second director of the Pasteur Institute after Pasteur's directorship.
Keywords: Duclaux, Émile, 1840-1904; Chemists; Microbiologists; Science; Portraits; Institut Pasteur (Paris, France); Pasteur, Louis, 1822-1895